Experimental and numerical investigation on the dynamic response of RC ultra-high piers under multiple impacts - Wang, J.; Xu, W.; Wang, J.; Chen, Y.; Huang, X.; Sun, Y.; Ahmed, Mizan; Chen, Wensu (2025)
In recent years, bridges with ultra-high piers (UHPs, the pier height of which ≥ 100 m) have been increasingly used in mountainous areas and may be subjected to impact loads such as rock falls. However, research on the impact performance of UHPs is very limited, and it is essential to understand their dynamic responses and failure modes under impact loads. In this study, we conducted a rare large-scale experimental investigation on a 1/20-scale UHP specimen subjected to multiple impact tests via a pendulum impact system. The failure mode, impact force, and displacement of the UHP specimen were recorded and analysed. On this basis, the numerical model of UHP was established and validated against the experimental results using LS-DYNA. And systematic numerical analysis was subsequently conducted to investigate the influence of parameters on the impact response of a scaled entire bridge with UHPs, including impactor diameter, axial load, impact height, and impact velocity. The results indicated that UHP predominantly exhibited flexural failure modes under mid-height impact. The lower local and overall stiffness of UHPs results in smaller impact forces compared to similar tests on medium and low-height piers. The increase in impactor diameter from 0.25b to 1.5b (b: pier section width) increased the impact force by approximately 54 %; meanwhile, the increase in impact velocity from 5 to 20 m/s boosted the impact force by roughly 157 % and reduced the impact duration by about 76 %. In contrast, a higher impact height reduced the peak shear force at the pier bottom by 35.6–47.4 %. The findings can be used as references for the anti-impact design of UHPs.